Role of frozen section in surgical management of ovarian neoplasm - Saphina Palakkan; Tony Augestine; M K Valsan; K P Abdul Vahab; Lekha K Nair (Wolters Kluwer Medknow Publications, 2020)
Objective: Cancers of the adnexae, including ovarian and fallopian tube, constitute the eighth most common cancers among women worldwide. Surgery remains the cornerstone in the management of ovarian cancer. Intraoperative frozen section diagnosis of ovarian tumors is widely used in making this distinction and to decide the course of surgery. Therefore, the accuracy of this technique is very important. The aim was to determine the overall accuracy, sensitivity, specificity, and predictive values of frozen section for ovarian tumors and to evaluate the role of frozen section in the surgical management of ovarian tumors. Materials and Methods: This was a descriptive longitudinal study conducted in the gynecology department of a tertiary care hospital. During the 1 ½ year period of data collection, frozen section was performed among 60 cases of ovarian neoplasms. The overall accuracy, sensitivity, specificity and predictive values of frozen section for benign, borderline and malignant categories of ovarian tumors were studied. Results: Out of the 60 patients of ovarian tumors, frozen section diagnosis showed that 43 (71.7%) tumors were benign, 11 (18.3%) were malignant and 6 (10%) were of borderline nature. Final histopathological diagnosis showed that 45 (75%) tumors were benign, 11 (18.3%) were malignant and 4 (6.7%) were borderline. Frozen section for benign tumors had 95% sensitivity, 100% specificity, 100% positive predictive value (PPV) and 88% negative predictive value (NPV). Malignant tumors had 90% sensitivity, 97% specificity, 90% PPV and 97% NPV with frozen section. However, frozen section had low sensitivity (75%) and PPV (50%) for borderline tumors. Specificity was 94% and NPV 98% in this group of tumors. Conclusion: Frozen section was found to be an accurate and useful modality in the intraoperative evaluation of patients with ovarian neoplasm. The results can help to decide the type and extent of surgery.